PENGARUH RETRIBUSI PASAR TERHADAP PENDAPATAN ASLI DAERAH DI KOTA GORONTALO - Ali, Yuwin; Daud, fatmawaty (JSAP : Journal Syariah and Accounting Public, 2019)
Economic development is regarded as a total increasing and per capita income which considers society development and followed by fundamental changes in economic structure of one country. Income of one country is encouraged become a source in a government development to increase society.Pembangunan ekonomi adalah suatu proses kenaikan pendapatan total dan pendapatan perkapita dengan memperhitungkan adanya pertambahan penduduk dan disertai dengan perubahan fundamental dalam struktur ekonomi suatu negara dan pemerataan pendapatan bagi penduduk suatu Negara